Efficacy of garlic (Allium sativum) on metabolic syndrome components in women with polycystic ovary syndrome: randomized controlled trial - Naiiere Gharagozloo Hesari; Shahideh Jahanian Sadatmahalleh; Parvin Mohebbi; Malihe Nasiri; Ahmad Khosravi (Journal of Health, Population and Nutrition)
Abstract Background This study aimed to illustrate the effect of garlic supplementation on metabolic syndrome (MetS) components in women with polycystic ovary syndrome (PCOS). Methods From 2020 to 2021, a randomized controlled clinical trial was conducted on 97 women with PCOS and MetS. Participants were randomly assigned to receive either garlic tablets (500 mg containing 2-3 mg allicin; n = 49) or placebo tablets (n = 48) twice daily for 8 weeks. The study assessed changes in MetS indices, quality of life (QoL), and sexual function before and after the intervention. Results After 8 weeks, the garlic group showed significant reductions in fasting blood sugar (FBS) by 10.5% (from 107.2 to 95.9 mg/dL; P < 0.001), triglycerides (TG) by 17.8% (P = 0.002), low-density lipoprotein cholesterol (LDL-C) by 14.2% (P < 0.001), total cholesterol (TC) by 12.6% (P < 0.001), and C-reactive protein (CRP) by 24.7% (P < 0.001), compared to the placebo group. A significant increase in sex hormone-binding globulin (SHBG) levels was also observed (18.3%; P = 0.005). Systolic and diastolic blood pressure decreased significantly by 5.2% and 6.1%, respectively (P < 0.001 and P = 0.001), and both weight and body mass index (BMI) were significantly reduced (P < 0.01). However, the waist-to-hip ratio (WHR) did not change significantly (P = 0.86). Notable improvements were also observed in all six domains of the Female Sexual Function Index (FSFI)— desire, arousal, lubrication, orgasm, satisfaction, and pain (P < 0.05 for all). Moreover, significant enhancements were recorded in all domains of the Modified Polycystic Ovary Syndrome Health-Related Quality of Life Questionnaire (MPCOSQ), including hirsutism, acne, weight, infertility, menstrual, and emotional disturbances (P < 0.001 for all). The study’s limitations include a relatively short follow-up period, lack of strict dietary control, and the omission of some relevant hormonal assays (e.g., androstenedione, DHEA, and DHEAS) due to budgetary constraints. Conclusions The results suggest that garlic supplementation may be an effective strategy for managing MetS markers in women with PCOS. Trial registration IRCT20150905023897N4, Registration date: 09/11/2019 ( https://irct.behdasht.gov.ir/trial/42316 ).